β-amyloid's neurotoxic mechanisms as defined by in vitro microelectrode arrays: a review - Aoife O'Connell; Leo Quinlan; Andrea Kwakowsky (Elsevier, 2024)
Alzheimer's disease is characterized by the aggregation of β-amyloid, a pathological feature believed to drive the neuronal loss and cognitive decline commonly seen in the disease. Given the growing prevalence of this progressive neurodegenerative disease, understanding the exact mechanisms underlying this process has become a top priority. Microelectrode arrays are commonly used for chronic, non-invasive recording of both spontaneous and evoked neuronal activity from diverse in vitro disease models and to evaluate therapeutic or toxic compounds. To date, microelectrode arrays have been used to investigate β-amyloids' toxic effects, β-amyloids role in specific pathological features and to assess pharmacological approaches to treat Alzheimer's disease. The versatility of microelectrode arrays means these studies use a variety of methods and investigate different disease models and brain regions. This review provides an overview of these studies, highlighting their disparities and presenting the status of the current literature. Despite methodological differences, the current literature indicates that β-amyloid has an inhibitory effect on synaptic plasticity and induces network connectivity disruptions. β-amyloid's effect on spontaneous neuronal activity appears more complex. Overall, the literature corroborates the theory that β-amyloid induces neurotoxicity, having a progressive deleterious effect on neuronal signaling and plasticity. These studies also confirm that microelectrode arrays are valuable tools for investigating β-amyloid pathology from a functional perspective, helping to bridge the gap between cellular and network pathology and disease symptoms. The use of microelectrode arrays provides a functional insight into Alzheimer's disease pathology which will aid in the development of novel therapeutic interventions.